Economic crop plantation advisory system in rubber-based intercropping - Makchan, Urairat; Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2020)
Plummeting demand and increasing production have triggered a fall in rubber prices. This may be due to the impact of technological progress that can evolve synthetic raw materials to replace the use of rubber in certain industries. There are a number of reasons that cause the rubber price crisis. Consequences are not only affecting rubber planters, but also causing a direct impact to the overall economy of the country. Various agencies have seriously sought ways to solve the problem to help rubber farmers. One simple and practical method that has been proposed is to grow some other crops in free spaces of rubber plantations. It is an excellent idea to transform a single rubber plantation into an integrated farmland, in which rubber planters will not have to rely only on one source of income. Pursuing the sufficiency economy philosophy, the main objective is to help rubber farmers earn greater incomes in a sustainable manner, particularly by improving the quality and quantity of their crops, while remaining firm in preserving natural resources, such as soil, water, and air. To make such solution achievable, the public and private sectors have conducted various researches on how to produce a greater yield on a given plot of land in a rubber plantation. Certain types of crops have been determined to be grown in rubber plantations. They are compatible crops, multiple crops, and economic crops, which can ensure increasing agricultural productivity throughout the rubber plantation period. This paper aims to present the analysis of data related to the cultivation of other crops in unoccupied areas of rubber plantations, where rubber farmers and relevant parties will be offered productive suggestions on rubber farming. For data that have been input to process in the advisory system such as soil, water, air, and alternative crop prices can be obtained from data online and data offline. The results from the system will be knowledge for rubber famers directly or agricultural specialists to provide rubber farmers with extensive knowledge on the benefits of transforming a single rubber plantation into an integrated farmland, as part of the goal to create greater income-earning opportunities by growing compatible crops, multiple crops, and economic crops.
Keywords: Data analytics; Information systems advisory system; Para rubber; Rubber; Web query